Evaluation of Weight Change During Carboplatin Therapy in Dogs With Appendicular Osteosarcoma. (15th May 2017) - Story, A.L.; Boston, S.E.; Kilkenny, J.J.; Singh, A.; Woods, J.P.; Culp, W.T.N.; Skorupski, K.A.; Lu, X.
Abstract : Background: The prevalence of cancer cachexia in veterinary medicine has not been studied widely, and as of yet, no definitive diagnostic criteria effectively assess this syndrome in veterinary patients. Objectives: (1) To determine the patterns of weight change in dogs with appendicular osteosarcoma treated with amputation and single‐agent carboplatin during the course of adjuvant chemotherapy; and (2) to determine whether postoperative weight change is a negative prognostic indicator for survival time in dogs with osteosarcoma. Animals: Eighty‐eight dogs diagnosed with appendicular osteosarcoma. Animals were accrued from 3 veterinary teaching hospitals. Methods: Retrospective, multi‐institutional study. Dogs diagnosed with appendicular osteosarcoma and treated with limb amputation followed by a minimum of 4 doses of single‐agent carboplatin were included. Data analyzed in each patient included signalment, tumor site, preoperative serum alkaline phosphatase activity (ALP), and body weight (kg) at each carboplatin treatment. Results: A slight increase in weight occurred over the course of chemotherapy, but this change was not statistically significant. Weight change did not have a significant effect on survival. Institution, patient sex, and serum ALP activity did not have a significant effect on survival. Conclusions and Clinical Importance: Weight change was not a prognostic factor in these dogs, and weight loss alone may not be a suitable method of determining cancer cachexia in dogs with appendicular osteosarcoma.